Biblioteki parafi alne dekanatów krakowskich: Lelów i Wolbrom w XVIII wieku - Jamioł, Piotr (Archiwa, Biblioteki i Muzea Kościelne, 2012)
The research and exploring of the old parish libraries allows us to understand the processes associated with their foundation and use. Visitations in the Diocese of Kraków carried on in the eighteenth century revealed that the parish clergy cared for the collection of books. Priests clearly appreciated books’ auxiliary role in teaching and preaching. This is confi rmed by quite a substantial collection of books in Lelów and Wolbrom deaneries. The large number of books on theology and preaching collected in some parishes indicates that the local parish and assistant priests were interested in reading. In addition to this the synod regulations and pastoral letters encouraged and supported the collecting of books. Church authorities rightly and wisely recognized the useful role of books in supporting pastoral work of the clergy. Therefore, the resolutions of the Synod of Bishops and pastoral letters pointed to the problem of access by the clergy to the most essential aid in preaching and hearing of confessions. Library resources were growing, mainly through individual donations, larger bequests and also by purchase. Initially, the priests created private collections of books according to their own needs or personal interests. Later on, they donated these books to parish libraries. These collections, consistent in their ideological content, refl ected the view of the people, who created the libraries and used them. They are a sign of a high intellectual culture of the book donors. As it is evident from the above fi ndings, in terms of the existence of parish libraries in the two deaneries the situation was quite good. Over time, their number and the number of books was increasing steadily. Figures from the source not only confi rm this, but also point to the fact that in general those collections were decreasing. This was associated with the widespread practice of expansion of the private collections by adding books from the church collection. In addition, many books were destroyed as a result of numerous fi res, invasions and theft. The fact of missing certain books, though not benefi cial to the church library is always an indicator that they were in use.